Gap junction modulation and its implications for heart function - Kurtenbach, Stefan; Kurtenbach, Sarah; Zoidl, Georg (Frontiers in Physiology, 2014)
Gap junction communication mediated by connexins is critical for heart function. To gain insight into the causal relationship of molecular mechanisms of disease pathology, it is important to understand which mechanisms contribute to impairment of gap junctional communication. Here, we present an update on the known modulators of connexins, including various interaction partners, kinases and signaling cascades. This gap junction network can serve as a blueprint for data mining approaches exploring the growing number of publicly available data sets from experimental and clinical studies.